Prevalence and predictors of chronic thromboembolic pulmonary hypertension following severe forms of acute pulmonary embolism - Pargana, Joana (2023)
© 2023 Sociedade Portuguesa de Cardiologia. Published by Elsevier Espa˜na, S.L.U. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).